Financial Inclusion in Rural Uganda: Testing Interaction Effect of Financial Literacy and Networks - Okello Candiya Bongomin, George; Mpeera Ntayi, Joseph; Munene, John C.; Nkote Nabeta, Isaac (Journal of African Business, 2016)
Based on the premise that financial literacy take place in networks to influence the level of financial inclusion, the study examined whether networks moderate in the relationship between financial literacy and financial inclusion among poor households in rural Uganda. Studies have revealed that financial literacy affects the level of financial inclusion. However, these studies have failed to incorporate the moderating role of networks in the relationship between financial literacy and financial inclusion. The results showed that networks positively and significantly moderates in the relationship between financial literacy and financial inclusion with both financial literacy and networks having direct and significant effects.
Keywords: Financial inclusion; Financial literacy; Microfinance; Social networks; Social ties